Implementasi Miniatur Smart Home Berbasis Internet of Things sebagai Media Pembelajaran Mikrokontroler - Erwinsius_Simamora Erwin; Adhinda Cynthia Gunawan; Muhammad Aulia Rahman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Learning in the Sensor and Transducer course requires a strong understanding of both theoretical concepts and practical applications. However, limited laboratory equipment, restricted practice time, and high operational costs often hinder the learning process. This study aimed to determine the effectiveness of Wokwi simulation media in improving students' learning outcomes in the Sensor and Transducer course. The research employed a quantitative approach using a one-group pretest-posttest design involving students of the Electrical Engineering Education Study Program at Universitas Negeri Medan. Data were collected through learning achievement tests and student response questionnaires. The results showed a significant improvement in students' average scores, increasing from 63.78 on the pretest to 94.72 on the posttest. Furthermore, the questionnaire results indicated that students responded very positively to the use of Wokwi as a learning medium because it is easy to use, interactive, and effective in helping them understand sensor concepts through practical simulation. Therefore, the implementation of Wokwi is effective in improving students' learning outcomes and can serve as an alternative technology-based learning medium for the Sensor and Transducer course.